Answer:y=4x+11
Step-by-step explanation:
Substitute the coordinates in each of the above equations,
Then the left hand side of the equation should be equal to the right hand side of the equation.
By substituting the above coordinates in the second answer,
-1= 4(-3)+11
-1=-1
Answer:
Noooo
Step-by-step explanation:
Answer:
4x -12
Step-by-step explanation:
Your question answers itself: you use the distributive property to remove the parentheses.
4(x -3) = 4(x) +4(-3) = 4x -12
Answer:
b
Step-by-step explanation:
gjhghjghj